Implementasi Pembelajaran Berdiferensiasi dengan Model Problem Based Learning pada Siswa Sekolah Dasar Kelas VI - Fitria Novita Sarie (Universitas Islam Nahdlatul Ulama Jepara, 2022)
No students in the class are the same. They come from different backgrounds, have different learning preferences, different interests, or learn at different speeds so their readiness to learn is different. Differentiated learning is learning made by teachers to meet the learning needs of students in the classroom. This learning practice is important to share because it is expected to provide benefits regarding the application of differentiated learning in elementary schools. Differentiated learning in this study uses the Problem Based Learning (PBL) model. PBL is a student-centered learning strategy that requires students to be skilled and sensitive to solving problems in their environment. The strategy used in this differentiated learning is to map learning needs based on three aspects, namely learning readiness, interest in learning, and student learning profiles by using surveys filled out via smart phones. Then the author plans differentiated learning based on the results of the mapping, namely providing various choices of strategies, materials, and ways of learning. The results of the learning that has been carried out are that students are very happy and enthusiastic in participating in learning from beginning to end. Differentiated learning that is carried out is able to accommodate the learning needs of students in one class.